“ENHANCING SPEAKING SKILLS THROUGH ONLINE APPLICATIONS” - Ismoilov Tuychiboy Furqatzoda (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores methods to enhance speaking skills by leveraging online applications. The study is organized into two main parts: Part 1 discusses technological tools and pedagogical frameworks, while Part 2 examines learner engagement and assessment strategies. Additionally, a minimized version of the short story “Hellados” is provided to illustrate interactive speaking tasks, followed by two exercises aimed at reinforcing comprehension and production. References and footnotes are included to support the theoretical and practical perspectives presented.